Molecular Docking Analysis of Hydroxy Chalcones and Flavones from Anisaldehyde and Veratraldehyde as EGFR Inhibitors: Predicting Anticancer Potential - Pambudi, Wisnu; Haryadi, Winarto; Matsjeh, Sabirin; Anwar, Chairil (Molekul, 2024)
This study aimed to investigate the potential of hydroxy chalcone and flavone derivatives as inhibitors of the epidermal growth factor receptor (EGFR) with anticancer properties. Molecular docking simulations were conducted using Autodock Tools 1.5.6 and Discovery Studio visualizer. The EGFR protein structure with the PDB code 1M17 was utilized as the receptor, explicitly targeting the binding pocket. Redocking of the reference ligand erlotinib yielded a binding energy of -7.51 kcal mol-1 with an RMSD of 0.54 Å, confirming the accuracy of the docking protocol. The hydroxy chalcone and flavone derivatives exhibited binding energies ranging from -6.50 to -7.67 kcal mol-1 when interacting with the EGFR protein. Among the studied compounds, compound 2',5'-dihydroxy-3,4-dimethoxychalcone (1g) displayed the lowest binding energy. Interactions involving amino acids such as Met769, Ala719, Thr766, Lys721, and Glu738 were identified as crucial hydrogen bonding interactions between the ligands and the EGFR protein. These findings suggest that 2',5'-dihydroxy-3,4-dimethoxychalcone holds strong potential as a tyrosine kinase inhibitor, positioning it as a promising candidate for further development as an anticancer agent. The outcomes of the computational analysis conducted through the pkCSM online platform indicated that the chemical 2',5'-dihydroxy-3,4-dimethoxychalcone had favorable pharmacokinetic characteristics and showed low toxicity levels. Keywords: molecular docking, hydroxy chalcone, flavone, egfr, ADMET